How do you rewrite \[5{x^{ - 4}}\] using positive exponents?
Answer
Verified
442.8k+ views
Hint: We will use the algebraic formula of indices to convert the expression of negative exponents into positive exponents. On doing some simplification we get the required answer.
Formula used: Multiplication rule of Indices:
If we multiply any variable \[n\]number of times, then we will put the addition of this \[n\]numbers into the power of that variable.
Like,
\[(m \times m \times m \times m \times ............n\;number\;of\;times)\]
\[ = {m^{(1 + 2 + 3 + 4 + ..... + n)}}\].
Division rule of Indices:
If we divide a variable having an exponent to its power by the same variable having a different exponent to its power, then we need to subtract the components in the power.
Like,
\[\dfrac{{{a^m}}}{{{a^n}}} = {a^{(m - n)}}\;,\;where\;m,n\;are\;any\;number.\]
If \[m = 0\], then we can set:
\[{a^m} = {a^0}\].
Which implies that \[{a^0} = 1\].
Now, we can derive the above equation as \[\dfrac{{{a^m}}}{{{a^n}}} = \dfrac{1}{{{a^n}}},\;when\;m = 0.\]
Complete Step by Step Solution:
We have to find the positive exponent of \[5{x^{ - 4}}\].
Let's say, \[A = 5{x^{ - 4}}\].
As we know \[(0 - 4) = - 4\], we can rewrite the above expression.
Now, we can expand it into \[{a^{m - n}}\]form in following way:
\[A = 5 \times {x^{(0 - 4)}}\], where \[5\]is the coefficient of the above expression.
So, if we tally this form with the above formula, we can write the following equations:
\[ \Rightarrow a = x,\;m = 0,\;n = 4.\]
So, we can write the above expression in following way:
\[ \Rightarrow A = 5 \times \dfrac{{{x^0}}}{{{x^4}}}\].
We know that, \[{x^0} = 1\].
By putting this value in the above expression, we get:
\[ \Rightarrow A = 5 \times \dfrac{1}{{{x^4}}}\].
We can rewrite it in following way:
\[ \Rightarrow A = \dfrac{5}{{{x^4}}}\].
So, in the above expression every value of the exponent is positive.
Therefore, The required positive exponent form of the expression \[5{x^{ - 4}}\] is \[\dfrac{5}{{{x^4}}}\].
Note: Alternative way to solve:
We can also use the multiplication property of indices.
It is given that \[5{x^{ - 4}}\].
Now, we can rewrite \[( - 4)\] as \[( - 1) + ( - 1) + ( - 1) + ( - 1)\].
So, we can rewrite \[5{x^{ - 4}}\] as \[5{x^{( - 1) + ( - 1) + ( - 1) + ( - 1)}}\].
By using the multiplication rule of indices, we can write the following expression:
\[ \Rightarrow 5 \times {x^{ - 1}} \times {x^{ - 1}} \times {x^{ - 1}} \times {x^{ - 1}}\].
We know that, \[{a^{ - n}} = \dfrac{1}{{{a^n}}}\].
So, we can rewrite \[5 \times {x^{ - 1}} \times {x^{ - 1}} \times {x^{ - 1}} \times {x^{ - 1}}\] as following way:
\[ \Rightarrow 5 \times \left( {\dfrac{1}{x} \times \dfrac{1}{x} \times \dfrac{1}{x} \times \dfrac{1}{x}} \right)\]
By simplifying it, we get:
\[ \Rightarrow \dfrac{5}{{{x^4}}}\].
So, required positive exponent form \[\dfrac{5}{{{x^4}}}\].
Formula used: Multiplication rule of Indices:
If we multiply any variable \[n\]number of times, then we will put the addition of this \[n\]numbers into the power of that variable.
Like,
\[(m \times m \times m \times m \times ............n\;number\;of\;times)\]
\[ = {m^{(1 + 2 + 3 + 4 + ..... + n)}}\].
Division rule of Indices:
If we divide a variable having an exponent to its power by the same variable having a different exponent to its power, then we need to subtract the components in the power.
Like,
\[\dfrac{{{a^m}}}{{{a^n}}} = {a^{(m - n)}}\;,\;where\;m,n\;are\;any\;number.\]
If \[m = 0\], then we can set:
\[{a^m} = {a^0}\].
Which implies that \[{a^0} = 1\].
Now, we can derive the above equation as \[\dfrac{{{a^m}}}{{{a^n}}} = \dfrac{1}{{{a^n}}},\;when\;m = 0.\]
Complete Step by Step Solution:
We have to find the positive exponent of \[5{x^{ - 4}}\].
Let's say, \[A = 5{x^{ - 4}}\].
As we know \[(0 - 4) = - 4\], we can rewrite the above expression.
Now, we can expand it into \[{a^{m - n}}\]form in following way:
\[A = 5 \times {x^{(0 - 4)}}\], where \[5\]is the coefficient of the above expression.
So, if we tally this form with the above formula, we can write the following equations:
\[ \Rightarrow a = x,\;m = 0,\;n = 4.\]
So, we can write the above expression in following way:
\[ \Rightarrow A = 5 \times \dfrac{{{x^0}}}{{{x^4}}}\].
We know that, \[{x^0} = 1\].
By putting this value in the above expression, we get:
\[ \Rightarrow A = 5 \times \dfrac{1}{{{x^4}}}\].
We can rewrite it in following way:
\[ \Rightarrow A = \dfrac{5}{{{x^4}}}\].
So, in the above expression every value of the exponent is positive.
Therefore, The required positive exponent form of the expression \[5{x^{ - 4}}\] is \[\dfrac{5}{{{x^4}}}\].
Note: Alternative way to solve:
We can also use the multiplication property of indices.
It is given that \[5{x^{ - 4}}\].
Now, we can rewrite \[( - 4)\] as \[( - 1) + ( - 1) + ( - 1) + ( - 1)\].
So, we can rewrite \[5{x^{ - 4}}\] as \[5{x^{( - 1) + ( - 1) + ( - 1) + ( - 1)}}\].
By using the multiplication rule of indices, we can write the following expression:
\[ \Rightarrow 5 \times {x^{ - 1}} \times {x^{ - 1}} \times {x^{ - 1}} \times {x^{ - 1}}\].
We know that, \[{a^{ - n}} = \dfrac{1}{{{a^n}}}\].
So, we can rewrite \[5 \times {x^{ - 1}} \times {x^{ - 1}} \times {x^{ - 1}} \times {x^{ - 1}}\] as following way:
\[ \Rightarrow 5 \times \left( {\dfrac{1}{x} \times \dfrac{1}{x} \times \dfrac{1}{x} \times \dfrac{1}{x}} \right)\]
By simplifying it, we get:
\[ \Rightarrow \dfrac{5}{{{x^4}}}\].
So, required positive exponent form \[\dfrac{5}{{{x^4}}}\].
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
How do you graph the function fx 4x class 9 maths CBSE
Name the states which share their boundary with Indias class 9 social science CBSE
Difference Between Plant Cell and Animal Cell
What is pollution? How many types of pollution? Define it
What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.